Gas Plasma Pre-treatment Increases Antibiotic Sensitivity and Persister Eradication in Methicillin-Resistant Staphylococcus aureus - Guo, Li; Xu, Ruobing; Zhao, Yiming; Liu, Dingxin; Liu, Zhijie; Wang, Xiaohua; Chen, Hailan; Kong, Michael G. (Frontiers in Microbiology, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of serious nosocomial infections, and recurrent MRSA infections primarily result from the survival of persister cells after antibiotic treatment. Gas plasma, a novel source of ROS (reactive oxygen species) and RNS (reactive nitrogen species) generation, not only inactivates pathogenic microbes but also restore the sensitivity of MRSA to antibiotics. This study further found that sublethal treatment of MRSA with both plasma and plasma-activated saline increased the antibiotic sensitivity and promoted the eradication of persister cells by tetracycline, gentamycin, clindamycin, chloramphenicol, ciprofloxacin, rifampicin, and vancomycin. The short-lived ROS and RNS generated by plasma played a primary role in the process and induced the increase of many species of ROS and RNS in MRSA cells. Thus, our data indicated that the plasma treatment could promote the effects of many different classes of antibiotics and act as an antibiotic sensitizer for the treatment of antibiotic-resistant bacteria involved in infectious diseases.